VALIDITAS DAN PRAKTIKALITAS MEDIA PEMBELAJARAN KOMIK UNIK DIGITAL BIOLOGI (KUDBI) BERBASIS ONLINE PADA MATERI VIRUS - Afidah, Mar’atul; Wahyuni, Sri; Rikizaputra, Rikizaputra; Yulanda, Vira Amelia (Universitas Lancang Kuning, 2024)
This research was concluded with the aim of developing online based Digital Biology Unique Comics (KUDBI) Learning Media on Virus material in class X Mathematics and Natural Sciences. This learning media was created to facilitate the teaching and learning process and to see feasibility of the online comic based learning media that has been developed. This research is a research development (Research And Development / R&D) with research subjects of class X MIPA students at SMAN 3 Pekanbaru. The research sample was taken using the Cluster Random Sampling technique, which is a sampling technique consisting of certain groups that have special qualifications in the population. Data collection method using validity and practicality questionnares, which will later be analyzed in the form of numbers, suggestions, critism, and input from research subject. The results showed that the percentage of material expert validity was 85% (very valid), media expert was 99% (very valid), linguist was 88% (very valid), and design expert was 100% (very valid). The practicality level of learning media by teachers is 94% (very practical), product trials on students get a percentage of 88.5% (very practical). From the results of the study, it can be concluded that the unique digital biology comics (KUDBI) learning media on Virus materials is suitable for use as a learning medium.